2021
DOI: 10.1371/journal.pone.0249216
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B virus among pregnant women attending Antenatal care in Dilla University Referral Hospital Gedio Zone, Ethiopia; health facility based cross-sectional study

Abstract: Introduction A pregnancy that has been complicated with Hepatitis B virus (HBV) infection results in typical management problems for both the mother and the newborn. One of the universal efforts in tackling the impact of chronic HBV is the prevention of mother-to-child transmission during Antenatal care via prompt screening as the majority of chronic infections globally harbored during this period. Rewarding result have been achieved in reducing this problem at this period of life through maternal screening pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
4
2
Order By: Relevance
“…A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ]. Some other research findings in Ethiopia and abroad revealed that the seroprevalence of HBV among the same study subjects was lower than that of the current study [ 6 , 13 , 19 , 20 , 34 ]. On the contrary, some other studies showed higher HBV infection rate among different population groups and among pregnant mothers.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…A cross-sectional study in Tanzania also reported consistent HBV infection rates among pregnant women [ 33 ]. Some other research findings in Ethiopia and abroad revealed that the seroprevalence of HBV among the same study subjects was lower than that of the current study [ 6 , 13 , 19 , 20 , 34 ]. On the contrary, some other studies showed higher HBV infection rate among different population groups and among pregnant mothers.…”
Section: Discussioncontrasting
confidence: 77%
“…Mother-to-child transmission of HBV, which might be via intrauterine transmission, is a common phenomenon and causes chronic infection of the virus [10]. The seroprevalence of HBV among pregnant women in Ethiopia ranges from 4.5% to 7.9%, that is in line with intermediate level of endemicity of the virus [11][12][13][14][15]. In most studies done in Ethiopia, the seroprevalence of HCV was lower than HBV and it ranges from 0.26% to 8.07% [9,[15][16][17].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, 52.2% of the pregnant HBV-positive women are co-infected with HIV/AIDS. Atalay et al [14] reported that among the pregnant women who participated in their study, 215 (91.1%) were screened for HIV on their antenatal visit, where 4.5% were positive and 1.86% for HBsAg. As in our findings, their study also found a significant relationship between the factors influencing the rate of transmission of HBV infection and HIV confection.…”
Section: Discussionmentioning
confidence: 99%
“…Some pregnant women may likely develop fulminant hepatitis, resulting in massive hepatic necrosis. About 10% of pregnant women positive for Hepatitis B virus infection may be chronic carriers, that can develop liver cirrhosis and hepatocellular carcinoma [13,14]. Viral (serum) hepatitis is responsible for a significant number of liver diseases globally and infected individuals can remain asymptomatic for many years.…”
Section: Introductionmentioning
confidence: 99%